1990
DOI: 10.1002/ajim.4700180213
|View full text |Cite
|
Sign up to set email alerts
|

1983 occupational injury hospital admissions in Iowa: A comparison of the agricultural and non‐agricultural sectors

Abstract: An occupational injury surveillance project was conducted in 15 of Iowa's 99 counties. Trained abstractors reviewed the medical records of persons admitted for trauma to hospitals during 1983. Based on these chart reviews, subsequent mail-out questionnaires and phone contacts were made, and rate estimates for occupational injury hospitalization for farmers and non-farmers were generated. The 1980 U.S. census data for occupation and market area data for the sample hospitals were used for the rate calculations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…In contrast, one statewide and one nine state study of all work-related injuries, reported rates that were highest for both the youngest and oldest extremes of age [Mitchell, 1998;Fuortes et al, 1990]. In this study, cuts, abrasions, and burns were highest in the 16±25 year old range and decline with increasing age.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast, one statewide and one nine state study of all work-related injuries, reported rates that were highest for both the youngest and oldest extremes of age [Mitchell, 1998;Fuortes et al, 1990]. In this study, cuts, abrasions, and burns were highest in the 16±25 year old range and decline with increasing age.…”
Section: Discussioncontrasting
confidence: 60%
“…(3) The pace of farm work is internally controlled; thus, older farmers can structure their workday according to their capabilities. For example, farmers who have suffered injuries return to work sooner than their industrial counterparts as they can maintain a pace that is consistent with their recovery [Fuortes et al, 1990]. Another objective of this study was to determine if older farmers modified their hours worked if they suffered from illness or were taking medications.…”
Section: Discussionmentioning
confidence: 99%
“…Tractors are also associated with a large number of nonfatal agricultural injuries [Cordes and Foster, 1988;Fuortes et al, 1990;May, 1990;Gerberich et al, 1991Gerberich et al, , 1993Gerberich et al, , 1998Gerberich et al, , 2003Brison and Pickett, 1992;Layde et al, 1995;Lee et al, 1996;Bancej and Arbuckle, 2000]. In 2001, a rate of 2.6 non-fatal, days-away-from-work tractor injuries per 10,000 full-time workers was reported for the agriculture, forestry, and fishing industry [United States Department of Labor, Bureau of Labor Statistics, 2003].…”
Section: Introductionmentioning
confidence: 99%